Delamination damage imaging method of CFRP composite laminate plates based on the sensitive guided wave mode. (15th February 2023) - Zhang, Hui; Sun, Jing; Rui, Xiaobo; Liu, Si
Abstract: This research is related to a detection and imaging method of delamination damage in CFRP composite laminate structures. Conventional guided wave detection methods often use the reflected wave signal at the defect as an indicator. However, the reflected wave signal caused by delamination damage is very weak compared with surface damage such as depressions, which brings great difficulty to delamination detection. The aim is to demonstrate a method for detecting delamination damage such that estimation of the morphology of the delamination can be obtained. This method uses full-wavefield data and is based on incident waves rather than reflected waves. This method weakens the original A0 mode through annular band-stop filtering, and at the same time enhances the sensitive modes in the full wavefield data. The intensity of enhanced signal in the time domain is used to image the delamination. The simulation model is used for modeling of guided waves propagation and interaction with delamination damage in CFRP composite laminate. The method is first illustrated on simulated data, and then tested on experimental results. It is shown that it is possible to visualize the delamination damage morphology by using the proposed SME imaging method.